A study of flare load reduction by a safety instrumented system based on a high integrity protection system. Issue 4 (3rd June 2013) - Lee, Inbok; Oh, Taekeun
<x xml:space="preserve">Abstract</x> In order to relieve the over‐pressure safely due to a process malfunction in the oil refineries and petrochemical plants, a flare system has been used in many cases. However, in some cases, it is not recommended to install an additional flare system because of various limitations such as environmental regulations and the lack of plant area. Moreover, it is also challenging to mitigate the increase of flare load due to the failure of instruments only by the existing flare system. So, the reduction of the flare load has been the center of attention. As a good solution to this problem, a safety instrumented system (SIS) can be used. The mitigation scheme for flare load by the SIS associated with the high integrity protection system has many advantages in theory, but several issues have to be checked before it is applied in reality. Thus, this study has suggested some technical basis and important factors to consider in the application to the actual safety design and operation process. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 393–400, 2013